A Qualitative Study of Hospitalists' Perceptions of Patient Satisfaction Metrics on Pain Management. Issue 1 (2nd January 2017) - Calcaterra, Susan L.; Drabkin, Anne D.; Doyle, Reina; Leslie, Sarah E.; Binswanger, Ingrid A.; Frank, Joseph W.; Reich, Jennifer A.; Koester, Stephen
ABSTRACT: Hospital initiatives to promote pain management may unintentionally contribute to excessive opioid prescribing. To better understand hospitalists' perceptions of satisfaction metrics on pain management, the authors conducted 25 interviews with hospitalists. Transcribed interviews were systematically analyzed to identify emergent themes. Hospitalists felt institutional pressure to earn high satisfaction scores for pain, which they perceived influenced practices toward opioid prescribing. They felt tying compensation to satisfaction scores commoditized pain. Hospitalists believed satisfaction would improve with increased time spent at the bedside. Focusing on methods to improve patient-physician communication, while maintaining efficiency in clinical practice, may promote both patient-centered pain management and satisfaction.